Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

jiji501

  • 3 years ago

How do I simplify 3a/a+3 - (a-4)/a-2

  • This Question is Closed
  1. JadeEyes
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Send the (a-4)/(a-2) to the other side. 3a/a+3 = (a-4)/(a-2) 3a/a + 3a/a = (a-4)/(a-2) (3a+3)/ a = (a-4)/(a-2) Then cross multiply. (3a+3)(a-2) = (a-4)(a) Solve. 3a^2 - 6a - 6 = a^2 -4a Make everything come to one side. 2a^2 - 2 - 6 = 0 Factorise. (2a +2)(a-3)= 0 Thus Either a = -1 or a= 3

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy